COMPARATIVE STUDY OF FINANCIAL AND ENVIRONMENTAL PERFORMANCE: INDONESIAN AND SINGAPOREAN E-COMMERCE COMPANIES - Eko Prasetyo; Nofryanti; Holiawati (ZILLZELL MEDIA PRIMA, 2025)
This study aims to analyze and compare the financial performance and environmental performance between local Indonesian e-commerce companies and foreign companies from Singapore operating in Indonesia. This study uses a mixed method, namely a quantitative approach with statistical analysis in the form of ANOVA One-Way test and Post Hoc Test on financial ratios (liquidity, profitability, solvency, and activity) as well as a qualitative approach through the analysis of the content of financial statements and sustainability reports based on Global Reporting Initiative (GRI) standards. The data used are derived from financial statements and sustainability reports for 2021–2023. The population of this study is e-commerce companies operating in Indonesia. The sample from this study is that ASEAN e-commerce companies operating in Indonesia have gone public both on the IDX and foreign stock exchanges, and have audited financial statements during 2021-2023. The results show that there are significant differences in several financial ratios between Indonesian and Singaporean companies. Foreign companies tend to have more efficient financial performance in terms of capital and asset management, as well as higher levels of environmental performance disclosure. This research contributes to the development of cross-border comparative literature in the digital sector, as well as being a practical reference for regulators and industry players in improving transparency and sustainability of company operations.